1995
DOI: 10.1111/j.1469-8749.1995.tb12035.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention by Magnesium of Exototoxic Neuronal Death in the Developing Brain: An Animal Model for Clinical Intervention Studies

Abstract: SUMMARY Excitotoxic disturbances during brain development were studied in the mouse using intracerebral injections of ibotenate, a glutamatergic agonist of the N‐methyl‐D‐aspartatc (NMDA) complex receptor, to analyse the protective effect of a systemic bolus of MgSO4. a non‐competitive antagonist of the NMDA ionophore‐complex receptor. MgSO4 did not prevent microgyia, induced by ibotenate when injected at PO immediately after the post‐migratory settlement of layer V, but did prevent ulegyrias. porencephalic cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
6

Year Published

1996
1996
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(39 citation statements)
references
References 31 publications
0
33
0
6
Order By: Relevance
“…Use of magnetic resonance imaging may have yielded better sensitivity than CUS in detecting subtle forms of WMI, but it was not routinely available in all the centres in 1997 in France. 22 The lack of a significant MgSO 4 effect in our PREMAG trial, despite its reported anti-inflammatory and antiexcitotoxic properties, [23][24][25][26][27] may be explained by the higher frequencies of PPROM and/or maternal-fetal infection observed in our MgSO 4 group that may have counterbalanced the neuroprotective effect of magnesium. Indeed, inflammatory processes, such as PPROM, chorioamnionitis, or maternal-fetal infection, have been reported to be associated with higher risks of periventricular leucomalacia.…”
Section: Discussionmentioning
confidence: 99%
“…Use of magnetic resonance imaging may have yielded better sensitivity than CUS in detecting subtle forms of WMI, but it was not routinely available in all the centres in 1997 in France. 22 The lack of a significant MgSO 4 effect in our PREMAG trial, despite its reported anti-inflammatory and antiexcitotoxic properties, [23][24][25][26][27] may be explained by the higher frequencies of PPROM and/or maternal-fetal infection observed in our MgSO 4 group that may have counterbalanced the neuroprotective effect of magnesium. Indeed, inflammatory processes, such as PPROM, chorioamnionitis, or maternal-fetal infection, have been reported to be associated with higher risks of periventricular leucomalacia.…”
Section: Discussionmentioning
confidence: 99%
“…Dans un modèle de lésions périnatales excitotoxiques mimant le spectre des lésions cérébrales acquises du prématuré (leucomalacie périventriculaire) et du nouveau-né à terme (accidents cortico-sous-corticaux), nous avons observé un effet protecteur du MgSO4 à certains stades du développe-ment cérébral. Injecté à cinq jours postnatals chez le souriceau, l'iboténate, un analogue du glutamate, induit des lésions mimant les leucomalacies périventriculaires du prématuré dont la taille est significativement diminuée en présence de MgSO 4 [25]. En revanche, la co-injection de MgSO 4 et d'iboténate est sans effet protecteur sur la survenue des lésions mimant celles du nouveau-né à terme lorsque l'iboténate est injecté à dix jours postnatals chez le souriceau (résultats non publiés).…”
Section: Intérêt Potentiel Du Magnésiumunclassified
“…Magnesium is recognized as a critical component in brain metabolism; however, the exact mechanism of action of magnesium sulphate in providing neuroprotection is not completely understood. It has been proposed that magnesium sulphate blocks the N-methyl-D-aspartate receptor 69 which in turn prevents the influx of calcium, maintains glutamate homeostasis and reduces interaction with oxygen-free radicals 70 . Magnesium sulphate also acts on the uteroplacental vascular system and promotes vasodilatation to maintain cerebral blood flow 71 .…”
Section: The Role Of Magnesium Sulphate and Antenatal Steroids In Impmentioning
confidence: 99%